THE EFFECTIVENESS OF ORAL CRYOTHERAPY TO REDUCE ORAL MUCOSITIS AMONG CANCER PATIENTS UNDERGOING CHEMOTHERAPY: A LITERATURE REVIEW: DOI: https://doi.org/10.35654/ijnhs.v2i2.108 - Elteria Sianturi; Dewi Irawati (International Journal of Nursing and Health Services (IJNHS), 2019)
Abstract Background: Oral cryotherapy has been scientifically proven as a non-pharmacological therapy to reduce the incidence of oral mucositis. With the decline in the incidence of oral mucositis, patient’s comfort improved, the length of stay and cost of care decreases, and maximum quality of life is achieved. Aim: To determine the effectiveness of oral cryotherapy in reducing the incidence of oral mucositis in patient undergoing chemotherapy. Method: This paper used literature review. The literature search was conducted of articles published from January 2012 through February 2018 using the PubMed, Embase, Cochrane Library and Ebscohost databases on the effectiveness of oral cryotherapy in reducing oral mucositis in patients undergoing chemotherapy. Result: This search resulted in a total of 8 articles. Evidence has indicated that there is a significance effect of oral cryotherapy in reducing oral mucositis. Conclusion: Oral cryotherapy is one of technique that easy to do, inexpensive and can be tolerated by patients in general, so it can be used widely. It can be used for adults and children with solid tumors, bone marrow transplant patients and for patients with different chemotherapy regimens (single or combination regimens). Keywords: Oral Cryotherapy, Oral Mucositis, Chemotherapy, patient’s quality of life